The Historical Development, Scholarly Research, And Contemporary Significance Of Miniature Art - Sa’dullayeva Nilufar Shorasul qizi (Peerian Journals Publishing, 2025)
This article analyzes the historical development, scholarly research, and contemporary significance of miniature art. The study employs historical sources, art historical approaches, and comparative analysis methods. The findings demonstrate that miniature art represents one of the highest achievements of Eastern culture and continues to hold an important place in modern cultural and artistic contexts
Keywords: Miniature art; historical development; Eastern culture